Pengaruh Struktur Modal, Likuiditas dan Kepemilikan Institusional Terhadap Agresivitas Pajak : (Studi Empiris Sub Sektor Makanan dan Minuman Yang Terdaftar di BEI Tahun 2017-2021) - Windi Anisah; Enan Trivansyah Sastri (AKUA: Jurnal Akuntansi dan Keuangan, 2023)
This research aims to determine the influence of capital structure, liquidity and institutional ownership on tax aggressiveness. Quantitative research methods with independent variables used in this research are capital structure, liquidity and institutional ownership. Meanwhile, the dependent variable is tax aggressiveness, measured using the effective tax rate (ETR). The data used in this research is secondary data, namely data obtained from the annual financial reports of companies listed on the Indonesia Stock Exchange (BEI) for the 2017-2021 period which can be obtained via the website www.idx.co.id. This research uses a purposive sampling method in determining the sample. As many as 19 of the 27 food and beverage sub-sector companies are listed on the Indonesian Stock Exchange. The data analysis method used in this research is multiple correlation analysis and multiple regression analysis. Data processing for this research uses eviews 9. The results of this research show that partially the variables of liquidity and institutional ownership have no effect on tax aggressiveness. Meanwhile, capital structure influences tax aggressiveness. The variables capital structure, liquidity and institutional ownership simultaneously influence tax aggressiveness.